Optimization of compatible mixed cultures for liquid state bioconversion of municipal wastewater sludge - Alam, Md. Zahangir; Fakhru’l-Razi, Ahmadun; Abd Aziz, Suraini; Mollla, Abul H (Kluwer Academic Publishers, 2003)

(untitled)
The filamentous fungal strains such as Penicillium corylophilum (P), Aspergillus niger (A), Trichoderma harzianum (T ) and Phanerochaete chrysosporium (PC) isolated from its relevant sources (wastewater, sewage sludge and sludge cake) were selected for compatible/incompatible mixed cultures. Six combinations of P. corylophilum and A. niger (P/A); P. corylophilum and P. chrysosporium (P/PC); P. corylophilum and T. harzianum (P/T ); A. niger and T. harzianum (A/T );A. niger and P. chrysosporium (A/PC); T. harzianum and P. chrysosporium (T/PC) were used to evaluate their potential performance as compatible/incompatible mixed culture for the treatment of municipal wastewater sludge in a bioconversion process. The results of the present study showed that the combinations of P/A, P/PC and A/PC showed compatible growth and the rest of the combinations (P/T , A/T and T/PC) were incompatible cultures. A maximum production of dry biomass and dry filter cake were recorded in the compatible mixed culture of P. corylophilum and A. niger (P/A). A maximum reduction of COD (90%) and a decreased filtration time of treated sludge was observed in the case of P/A microbial mixed culture. The pH value was also affected by the fungal cultures. Effective results were observed by using microbial mixed culture after four days of treatment compared to other treatments (2 and 6 days).